Financial literacy and behavioural biases of individual investors: Empirical evidence of Pakistan stock exchange - Nosheen Rasool; Safi Ullah (Journal of Economics, Finance and Administrative Science, 2020)
Purpose - Financial literacy is a crucial element of financial decision-making, exerting significant influence on the behaviour of individual investors, while making budgetary, house financing, stock investing and retirement planning decisions. So, the purpose of this research is to determine the relationship between financial literacy and behavioural biases of individual investors in Pakistan. Design/methodology/approach - In this research paper, a sample of 300 observations was obtained through questionnaires from individual investors residing in Lahore and invested in Pakistan Stock Exchange. The data obtained, was passed through Cronbach's Alpha and Exploratory Factor Analysis (EFA). The hypothesis developed for the research was tested by Pearson's Chi-square and Ordinal Regression Analysis. Findings - The hypothesis testing of the research concluded that there is a negative association between financial literacy and behavioural biases of individual investors. So, it means; with an increase in level of financial literacy, the likelihood of investor facing behavioural biases reduces. It also appeared that male respondents have more financial literacy than female respondents Originality/value - Previous studies in the field of finance, identified different factors causing the financial behaviour of individual investor of Pakistan, and also focused on level of financial literacy in Pakistan, but these studies have not emphasized the crucial relationship between financial literacy and behavioural biases of individual investors. Thus, the unique empirical analysis developed in this paper has accentuated the financial literacy as a factor that mitigates behavioural biases of individual investor.
Keywords: 330; Behavioural biases; Behavioural finance; Financial decision-making; Financial literacy; Individual investor